Progressive risk assessment of polychlorinated biphenyls through a Total Diet Study in the Korean population. (December 2015) - Shin, Eun-su; Nguyen, Khanh-Hoang; Kim, Jongchul; Kim, Cho-il; Chang, Yoon-Seok
Abstract: Human exposure to polychlorinated biphenyls (PCBs) from foods was investigated through a Total Diet Study (TDS) for the first time in Korea. A representative food list was developed from food intake data. Non-selected foods were also included in the TDS through the mapping process to anticipate practical risk assessment. For better representativeness, data (2008–2011) from the Korea National Health and Nutrition Examination Survey (KNHANES) were combined with the TDS data set. And also, we estimated the dietary exposure to PCBs from various food items using a 'best-fit' mapping process and assessed the differences in PCB exposures by sex and age. In this study, we examined total PCBs (62 congeners) including dioxin-like PCBs (DL-PCBs) and indicator PCBs, which are congeners that are mainly detected in various environmental matrices. The average dietary exposure (3.94 ng/kg body weight/day) that was estimated through food intake was 19.7% of the World Health Organization (WHO) recommendation. Highlights: A total of 282 samples, composed of the most consumed foodstuffs in Korea, were analysed and shown in detail. The contamination status of total PCBs in food was assessed, through their various condition on cooking methods. The dietary intakes of PCBs in various food groups were estimated in different region, gender and age groups. The improved and systematic food selection process was applied such as 'mapping process'. Abstract : This study is to ensure food safety through total analysis of PCBs with the improved risk assessment method.